(untitled) (Philological Studies, 2019)
Cultural and artistic associations are an important part of the scientific study of Macedonia’s cultural history. In this paper, I make a review of the occurrence of cultural-artistic associations, which were active in urban and rural areas from the beginning of the Macedonian nation state to the devastating earthquake in Skopje, based on archive materials and existing literature.